1987
DOI: 10.1007/bf00318723
|View full text |Cite
|
Sign up to set email alerts
|

The human arm as a redundant manipulator: The control of path and joint angles

Abstract: Abstract. The movements studied involved moving the tip of a pointer attached to the hand from a given starting point to a given end point in a horizontal plane. Three joints -the shoulder, elbow and wristwere free to move. Thus the system represented a redundant manipulator. The coordination of the movements of the three joints was recorded and analyzed. The study concerned how the joints are controlled during a movement. The results are used to evaluate several current hypotheses for motor control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 190 publications
(48 citation statements)
references
References 9 publications
3
44
1
Order By: Relevance
“…The aim of the current investigation was to look for measurable values corresponding to the hypothetical cost functions which were postulated earlier for the control of the redundant arm (Cruse 1986;Cruse and Briiwer 1987). The first question investigated was whether the choice of the arm position depends solely on the values of the joint angles or also on the length of the limbs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aim of the current investigation was to look for measurable values corresponding to the hypothetical cost functions which were postulated earlier for the control of the redundant arm (Cruse 1986;Cruse and Briiwer 1987). The first question investigated was whether the choice of the arm position depends solely on the values of the joint angles or also on the length of the limbs.…”
Section: Discussionmentioning
confidence: 99%
“…As described in two earlier papers (Cruse 1986, Cruse andBriiwer 1987), the movement of the arm is restricted to the horizontal plane and the three joints at shoulder, elbow and wrist are free to move. To measure the values of the joint angles the arm of the subject was laid on an artificial arm having three joints which was free to glide over a horizontal plane.…”
Section: Methodsmentioning
confidence: 99%
“…However, it predicts a bimodal velocity profile which is at odds with the experimental data (Atkeson and Hollerbach 1985). Later it was suggested that the hand trajectory is the result of a compromise between planning a straight line in the task space and planning a straight line in the joint space (Cruse and Brüwer 1987;Okadome and Honda 1999;Hersch and Billard 2007). Such hybrid computations offer numerous advantages for controlling 3-dimensional reaching movements, such as avoiding singularities and avoiding hitting the joint limits (Hersch and Billard 2007).…”
Section: Computational Approachmentioning
confidence: 99%
“…Various authors proposed more objective measures including specific limitations of motions (Van Thiel, et al 1999, Kawato 1996, Kawato and Wolpert 1998, Uno, et al 1989, Bruwer 1987 andCruse 1990) on which impairment is often largely based (e.g., AMA Guides to the Evaluation of Permanent Impairment [AMA 1997]). The reader is also referred to the recent comparison of commercially available measuring systems (Richards 1998).…”
Section: Introductionmentioning
confidence: 99%